Going around in circles: virulence plasmids in enteric pathogens - Pilla, G; Tang, C (Springer Nature, 2018)
Plasmids have a major role in the development of disease caused by enteric bacterial pathogens. Virulence plasmids are usually large (>40 kb) low copy elements and encode genes that promote host–pathogen interactions. Although virulence plasmids provide advantages to bacteria in specific conditions, they often impose fitness costs on their host. In this Review, we discuss virulence plasmids in Enterobacteriaceae that are important causes of diarrhoea in humans, Shigella spp., Salmonella spp., Yersinia spp and pathovars of Escherichia coli. We contrast these plasmids with those that are routinely used in the laboratory and outline the mechanisms by which virulence plasmids are maintained in bacterial populations. We highlight examples of virulence plasmids that encode multiple mechanisms for their maintenance (for example, toxin–antitoxin and partitioning systems) and speculate on how these might contribute to their propagation and success.